La organización, promoción y proyección de las Matemáticas en Costa Rica (ING) - De Faria, Edison (2003)
In this paper we describe initiatives and efforts realized by groups of people, organizations and Costa Rican institutions in benefit of the development and projection of mathematics in Costa Rica